Spring Into HTML and CSS - Holzschlag, Molly (Addison-Wesley Professional, 2005)
The fastest route to true HTML/CSS mastery! Need to build a web site? Or update one? Or just create some effective new web content? Maybe you just need to update your skills, do the job better. Welcome. This book's for you. We'll leverage what you already know about the web, so you'll go further, faster than you ever expected. You'll master today's best practices: the real nuts and bolts, not theory or hooey. You'll learn through dozens of focused HTML, XHTML, and CSS examples: crafted for simplicity and easy to adapt for your own projects. Need specific solutions? This book's modular, visual, high-efficiency format delivers them instantly . Molly E. Holzschlag draws on her unparalleled experience teaching Web design and development. No other HTML/CSS guide covers this much, this well, this quickly. Dig in, get started, get results! All you need to succeed with HTML, XHTML, and CSS in real-world projects Learn how to build web pages that'll work in any environment, on virtually any contemporary browser Construct templates that simplify every page you develop Structure and tag text so it's easy to work with and manage Add images, media, and scripts-quickly and reliably Discover the right ways to use HTML tables Build easy-to-use forms and validate your users' input Use CSS to take total control over your site's look and feel Master core CSS techniques: color, images, text styles, link effects, lists, navigation, and more Control margins, borders, padding, positioning, floats, even Z-index Design efficient, compatible, easy-to-manage CSS layouts Includes concise XHTML and CSS annotated references: quick help for every language element Spring Into... is a new series of fast-paced tutorials from Addison-Wesley. Each book in the series is designed to bring you up to speed quickly. Complex topics and technologies are reduced to their core components, and each component is treated with remarkable efficiency in one- or two-page spreads. Just the information you need to begin working...now! And because the books are example-rich and easy to navigate, you'll find that they make great on-the-job references after you've mastered the basics. © Copyright Pearson Education. All rights reserved.